Chapter 6. Cole Crop Production - Bonnie Wells; Hugh Smith; Lincoln Zotarelli; Peter J. Dittmar; Nicholas Dufault; Johan Desaeger; Qingren Wang (EDIS, 2022)
Chapter 6 of the Vegetable Production Handbook.